Financing Development Through Future-Flow Securitization - Ratha, Dilip (World Bank, Washington, DC, 2012)
Securitization of future hard currency receivables, that is, converting them into tradable securities, can allow developing country borrowers with good credit to overcome sovereign credit ceilings, and raise financing in international capital markets. The note examines the case of PEMEX, Mexico's state-owned oil and gas company, which in 1998 issued oil export-backed securities that received higher ratings from international credit rating agencies than Mexico's sovereign debt. Relative to unsecured debt, securitization lowered interest rates on PEMEX borrowing by 50-338 basis points (0.50-3.38 percentage points). Another example offered is the case of Banco de Credito in Peru, whose overseas Master Trust in the Bahamas (an offshore account) makes principal, and interest payments, forwarding excess collections to its headquarters in Peru. To increase investor confidence, the amount of future-flow receivables transferred to the trust was set at 2.5 times debt service requirements. In 1998 this transaction setup received an AAA credit rating from Standard & Poor's - higher than Peru's sovereign credit rating.